PENYELESAIAN SENGKETA KONSUMEN MELALUI UPAYA MEDIASI OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN DI KOTA SAMARINDA - Nur’Aina Rahmarida (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractConsumer Dispute resolution agency (BPSK) under Act No. 8 of 1999 on consumer Protection established by the Government, is the body in charge of handling and resolving disputes between consumers and business actors. The establishment of BPSK is to cope with the process of litigation that is old, formal and complicated by the alternative path of dispute resolution outside the judicial Court of fast, simple and inexpensive cost.The method used is a sociological juridical method, which presents a statement in the field of the legal rules contained in the regulations or legislation in force. Furthermore, data is analyzed qualitatively.The result of the research that authors do this process of consumer report to the consumer Dispute resolution agency (BPSK) of Samarinda City, consisting of several stages, the first phase of the consumer filing a report on verbal written dispute resolution or Written to the secretariat of BPSK. Under Law No. 8 of 1999 on consumer protection can be pursued using litigation and non litigation lines, settlement through non-litigation pathways is conducted by BPSK by mediation, conciliation and arbitration. Settlement of consumer disputes regarding the form and the amount of indemnification is submitted entirely to the parties.